2014
DOI: 10.1115/1.4028764
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pore to Throat Size Ratio on Interfacial Heat Transfer Coefficient of Porous Media

Abstract: In this study, the effects of pore to throat size ratio on the interfacial heat transfer coefficient for a periodic porous media containing inline array of rectangular rods are investigated, numerically. The continuity, Navier-Stokes, and energy equations are solved for the representative elementary volume (REV) of the porous media to obtain the microscopic velocity and temperature distributions in the voids between the rods. Based on the obtained microscopic temperature distributions, the interfacial convecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 21 publications
3
12
0
Order By: Relevance
“…A good agreement between the present results and those reported studies can be observed. The results of the present study are also validated by comparing with the relationship suggested in the study of Ozgumus and Mobedi (2015) as shown in Figure 3(c). The correlation in their study was given for forced convection heat transfer when Re changes between 1 and 100.…”
Section: Validation Of Obtained Numerical Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…A good agreement between the present results and those reported studies can be observed. The results of the present study are also validated by comparing with the relationship suggested in the study of Ozgumus and Mobedi (2015) as shown in Figure 3(c). The correlation in their study was given for forced convection heat transfer when Re changes between 1 and 100.…”
Section: Validation Of Obtained Numerical Resultssupporting
confidence: 79%
“…For instance, Kuwahara et al (2001) numerically studied the interfacial convective heat transfer coefficient for forced convection in a periodic porous medium consisting of square rods with staggered arrangement under local thermal non-equilibrium. Similar studies for the effect of different parameters were performed by Nakayama et al (2002), Ozgumus and Mobedi (2015), Petrasch et al (2008), Saito and de Lemos (2005), Teruel and Díaz (2013) and Gamrat et al (2008). Furthermore, Rees (2010) performed microscopic study on a composite solid saturated with a single fluid to calculate values for the interface heat transfer coefficient; however, the effect of fluid flow was not considered.…”
mentioning
confidence: 88%
“…H) is selected as characteristic length to define Nusselt number. The same behavior is also observed in numerous other reported studies (Kuwahara et al, 2000, Ozgumus andMobedi, 2014). Furthermore, to compare the Nusselt number of dual scale with mono-scaled porosity, equation 19is modified.…”
Section: Governing Equations and Boundary Conditions For Determinatiosupporting
confidence: 79%
“…The porous media with square rods in in-line arrangement and porosity of 0.75 is created. After solving the equations, the interfacial Nusselt numbers found for this porous media are compared with the results of Ozgumus and Mobedi (2014), Kuwahara et al (2000), Penha et al (2011) and Gamrat et al (2008) and the comparison is shown in Figure 5. As demonstrated in Figure 5, there is an excellent agreement between the results of the present study and the literature results for an extensive variety of Reynolds number.…”
Section: Resultsmentioning
confidence: 99%
“…This pattern is clearly visible in numerical investigations that were conducted using a pore-scale approach (e.g., Refs. [16][17][18]) and especially in those studies that took a macroscopic modeling approach (e.g., Refs. [19][20][21][22]).…”
Section: Introductionmentioning
confidence: 99%